Inhibition of Dll4-mediated signaling induces proliferation of immature vessels and results in poor tissue perfusion - Scehnet, Jeffrey S. (American Society of Hematology, 2007)
Vascular development is dependent on various growth factors and certain modifiers critical for providing arterial or venous identity, interaction with the surrounding stroma and tissues, hierarchic network formation, and recruitment of pericytes. Notch receptors and ligands (Jagged and Delta-like) play a critical role in this process in addition to VEGF. Dll4 is one of the Notch ligands that regulates arterial specification and maturation events. In the current study, we have shown that loss of function by either targeted allele deletion or use of a soluble form of Dll4 extracellular domain leads to inhibition of Notch signaling, resulting in increased vascular proliferation but defective maturation. Newly forming vessels have thin caliber, a markedly reduced vessel lumen, markedly reduced pericyte recruitment, and deficient vascular perfusion. sDll4 similarly induced defective vascular response in tumor implants leading to reduced tumor growth. Interference with Dll4-Notch signaling may be particularly desirable in tumors that have highly induced Dll4-Notch pathway.